Une enquête au cœur de l’œuvre flaubertienne : les études critiques et génétiques de Giovanni Bonaccorso - Stella Mangiapane (Flaubert: Revue Critique et Génétique)
This article illustrates the innovative issues and achievements of the critical and genetic studies Giovanni Bonaccorso conducted on Flaubert’s works. We will follow the evolution of his critical vision of Flaubert’s aesthetics, highlighting the principal characteristics of his investigative methodology. We will particularly concentrate on Bonaccorso’s fundamental work: the three volumes of the Corpus Flaubertium, a diplomatic and genetic edition of the manuscripts of the Trois Contes, the first to reveal to scholars the complete genesis of the great Norman writer’s oeuvre.